Analysis of the incidence and influencing factors of abdominal distension in postoperative lung cancer patients in ICU based on real-world data: a retrospective cohort study - Liu, Yan; Tang, Tingting; Wang, Chunyan; Wang, Chunmei; Zhu, Daxing (BMC surgery, 2024)
Abdominal distension is a relatively common complication in postoperative lung cancer patients, which affects patients' early postoperative recovery to varying degrees. However, the current status of the incidence of abdominal distension in postoperative lung cancer patients and the affecting factors are not well understood. This study aims at exploring the incidence of abdominal distension in postoperative lung cancer patients in ICU based on real-world data and analyzing its influencing factors. A retrospective cohort study was conducted, encompassing patients who underwent lung cancer resections in the Lung Cancer Center of West China Hospital of Sichuan University from April 2020 to April 2021. Nevertheless, patients younger than 18 years and those whose information was limited in medical records were excluded. All data were obtained from the hospital HIS system. In this study, the influencing factors of abdominal distension were analyzed by univariate analysis and multiple logistic regression methods. A total of 1317 patients met eligibility criteria, and were divided into the abdominal distended group and the non-distended group according to whether abdominal distension occurred after surgery. Abdominal distension occurred in a total of 182 cases(13.8%). The results of the univariate analysis showed that, compared with the non-distended group, the abdominal distended group had these features as follows: more women (P = 0.021), older (P = 0.000), lower BMI (P = 0.000), longer operation duration (P = 0.031), more patients with open thoracotomy (P = 0.000), more patients with pneumonectomy (p = 0.002), more patients with neoadjuvant chemotherapy (P = 0.000), more days of hospitalization on average (P = 0.000), and higher costs of hospitalization on average (P = 0.032). Multifactor logistic regression analysis showed that sex (OR = 0.526; 95% CI = 0.378 ~0.731), age (OR = 1.154; 95%CI = 1.022 ~1.304) and surgical approach (OR = 4.010; 95%CI = 2.781 ~5.781) were independent influencing factors for the occurrence of abdominal distension in patients after lung cancer surgery in ICU. The incidence of abdominal distension was high in postoperative lung cancer patients in ICU, and female, older and patients with open thoracotomy were more likely to experience abdominal distension. The study was approved by the Chinese Clinical Trials Registry (registration number was ChiCTR2200061370).